A Systematic Review Of RME Data Privacy And Security - Ikawati, Fita Rusdian; Ansyori, Anis (Universitas Muhammadiyah Sidoarjo, 2024)
Education (RME), where sensitive data pertaining to individuals and institutions is frequently collected, analyzed, and stored. The systematic review of RME data privacy and security is not only timely but also crucial for understanding the current landscape, identifying gaps, and proposing frameworks to enhance data protection measures. This research aims to analyze A Systematic Review Of RME Data Privacy And SecurityThis type of research is a literature review.. In this research conducted 15 journal literacy study regarding RME Data Privacy And Security. Data collection techniques using documentation from journals on Google Schoolar. Data analysis technique using Systemic Literature Review (SLR).The results of the study are The systematic review of RME data privacy and security revealed several critical areas requiring attention. Firstly, it was evident that current data handling practices often fall short of ensuring comprehensive privacy and security, posing risks to both researchers and participants. Additionally, there is a noticeable lack of standardized protocols across different institutions, leading to inconsistent protection measures. To address these issues, it is recommended that educational institutions adopt unified, stringent data privacy frameworks that comply with international standards. Furthermore, continuous training for researchers on data security best practices should be mandated to keep pace with evolving threats. By implementing these measures, the integrity of research data can be preserved, thereby fostering a more secure and trustworthy research environment.